2002
DOI: 10.1183/09031936.02.00211102
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant apoprotein A modulates interleukin-8 and monocyte chemotactic peptide-1 production

Abstract: Previous studies have shown that surfactant apoprotein A (SP-A) and natural or synthetic surfactant can modulate the release of pro-inflammatory cytokines from alveolar mononuclear phagocytes.The aim of this study was to assess whether SP-A or Surfactant (Surf) from patients with pulmonary alveolar proteinosis (PAP) can affect the release of two chemokines (interleukin (IL)-8 and monocyte chemtactic peptide (MCP)-1) from human monocytes and rat lung type-II cells. In addition IL-8 and MCP-1 levels were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…An example of this is evidence obtained in laboratory studies of SP‐A's actions on cytokine production. Specifically, addition of SP‐A to macrophage‐like cells in vitro has been shown to result in a dose‐dependent increase in IL‐1β, IL‐8, and other cytokines . Our finding that both SP‐A and IL‐1β and IL‐8 levels are highest in the early follicular phase when there is maximum need for protection suggest a similar role for SP‐A also in vivo .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…An example of this is evidence obtained in laboratory studies of SP‐A's actions on cytokine production. Specifically, addition of SP‐A to macrophage‐like cells in vitro has been shown to result in a dose‐dependent increase in IL‐1β, IL‐8, and other cytokines . Our finding that both SP‐A and IL‐1β and IL‐8 levels are highest in the early follicular phase when there is maximum need for protection suggest a similar role for SP‐A also in vivo .…”
Section: Discussionmentioning
confidence: 50%
“…Innate immune molecules such as SP‐A are recognized to provide the first line of defense against invasion of the host by pathogens . Their functions include an ability to recruit adaptive components of host defenses . An example of this is evidence obtained in laboratory studies of SP‐A's actions on cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…We included a total of 26 Table 2. Neutrophilic and eosinophilic alveolitis was observed in BOS patients as compared with stable LTRs.…”
Section: Bal Featuresmentioning
confidence: 99%
“…Previous studies have shown that presence of IL-8 in clinical samples is associated with lung disease. Therefore, it is proposed that controlling IL-8 level may be a feasible therapeutic strategy for management of lung disease (11,12). Exogenous lung surfactant (ELS) obtained from natural sources is a valuable drug candidate in neonatal respiratory distress syndrome and other respiratory disorders (13).…”
Section: Introductionmentioning
confidence: 99%